Trust and citizenship from global perspective - RHEE, Flora (KDI School, 2017)
Technological innovation has significantly reduced the time and distance across borders in the time of the 21st century. Nowadays more and more ordinary citizens are involved in the transnational integration of the world, and the flow of globalization seems to have diminished the role of the national state in protecting the legal rights of its citizens. At the same time, radical changes, such as immigration and an aging population, are bringing about a structural rearrangement in the entire world, with no exception of Asian society. This change suggests that the relationship between the state and civil society has become more important than ever. From this perspective, the trust relationship within civil society could be seen as an answer to socio-political uncertainties, since trust is known to be a key factor in maintaining a stable relationship within society. This study examines the conceptual framework of the existing literature on trust and citizenship, followed by an empirical study on Korea, Singapore, and Taiwan, countries that share similar development paths and rapid economic growth experiences, often described as the “Asian miracle.” Using the fourth wave of the Asian Barometer Survey (ABS) from the respective countries, this study statistically verifies the hypotheses via factor analysis, chi-square tests, analysis of variance (ANOVA) tests, Pearson’s and Kendall’s correlations, binary logistic regression, and multiple linear regression. In conclusion, the findings of this study suggest that in Korea, Singapore, and Taiwan, the level of interpersonal and institutional trust is highly correlated with the perception of national value. Also, contrasting results suggest that interpersonal trust is expressed in Taiwan as conventional citizenship such as voting and active participation, while in Korea and Singapore, this type of trust has led to an open attitude towards globalization and immigrant populations.
Thesis(Master) --KDI School:Master of Development Policy,2017